2017
DOI: 10.3390/molecules22071075
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Production of Pentacyclic Triterpenoid Compound Betulinic Acid from Betulin by the Engineered Saccharomyces cerevisiae

Abstract: Betulinic acid is a product of plant secondary metabolism which has shown various bioactivities. Several CYP716A subfamily genes were recently characterized encoding multifunctional oxidases capable of C-28 oxidation. CYP716A12 was identified as betulin C-28 oxidase, capable of modifying betulin. This study aimed to induce the transformation of betulin to betulinic acid by co-expressing enzymes CYP716A12 from Medicago truncatula and ATR1 from Arabidopsis thaliana in Saccharomyces cerevisiae. The microsome prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The supernatant was centrifuged at 12,000 rpm for 20 min, and the liposome precipitate was combined with methanol and chloroform (1:1) to destroy the structure. The content of betulin in the liposomes was determined referring to the method of Wu et al [33] as detection wavelength 210 nm, Reverse C18 Column (250 mm × 4.6 mm id, 4 μm; Waters), mobile phase acetonitrile: water = 91:9, flow rate 1.0 mL/min under 30 °C. Encapsulation efficiency of the liposomes was calculated by the following formula:EE (%) = (encapsulated betulinic acid)/(encapsulated betulinic acid+unencapsulated betulinic acid) × 100%…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was centrifuged at 12,000 rpm for 20 min, and the liposome precipitate was combined with methanol and chloroform (1:1) to destroy the structure. The content of betulin in the liposomes was determined referring to the method of Wu et al [33] as detection wavelength 210 nm, Reverse C18 Column (250 mm × 4.6 mm id, 4 μm; Waters), mobile phase acetonitrile: water = 91:9, flow rate 1.0 mL/min under 30 °C. Encapsulation efficiency of the liposomes was calculated by the following formula:EE (%) = (encapsulated betulinic acid)/(encapsulated betulinic acid+unencapsulated betulinic acid) × 100%…”
Section: Methodsmentioning
confidence: 99%
“…In terms of BA biosynthesis, two major steps are to be distinguished-lupeol synthesis by 2,3-oxidosqualene cyclisation and, subsequently, oxidation in the C 28 position by the enzymes of cytochrome P450 (CYP) (Wu et al 2017). Several genes encoding the enzymes critical for these reactions have been characterised.…”
Section: Betulinic Acidmentioning
confidence: 99%
“…For example, fatty acids of Coix lacryma-jobi oil increased polysaccharide production by directly affecting the synthesis level of phosphoglucose isomerase and α-phosphoglucomutase at different stage [ 10 ]. BA is synthesized mainly via the mevalonate pathway where acetyl-CoA is converted through a series of chemical reactions to 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA), to mevalonate (MVA), to isopentenyl-pyrophosphate (IPP), to farnesyl diphosphate (FPP), to squalene, and finally to betulinic acid [ 7 , 12 ]. Some enzymes are involved in the synthesis of betulinic acid including HMG-CoA synthase (HMGS), HMG-CoA reductase (HMGR), farnesyl pyrophosphate synthase (FPS) and squalene synthase (SQS) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Betulin is the precursor material of BA. In recent times, several reports have demonstrated that BA could be prepared through biotransformation process [ 11 , 12 , 13 ]. Meanwhile, betulin was used stimulatory agent to enhance mycelial biomass and production of exo-polysaccharides from I. obliquus [ 8 ].…”
Section: Introductionmentioning
confidence: 99%